Accumulation of cadmium in soils, litter and leaves in cacao farms in the North Sierra Nevada de Santa Marta, Colombia - Guarín, Daniel; Martin Lopez, Javier M; Libohova, Zamir; Benavides-Bolaños, Jhony; Maximova, Siela N; Guiltinan, Mark J; Spargo, John; Silva, Mayesse Aparecida da; Fernandez, Alejandro; Drohan, Patrick (Elsevier, 2024)
Cadmium (Cd) accumulation in Colombian cacao is a growing concern due to its potential health impacts and EU regulations on Cd content in chocolate products. Furthermore, cacao plays a significant role as an agricultural commodity and a tool for illegal crop replacement, yet our regional understanding of Cd dynamics in cacao cultivation in the north flank of the Sierra Nevada de Santa Marta is still limited. This research provides the first comprehensive investigation of cadmium biogeochemistry in cacao agroecosystems by analyzing the interactions between subsurface soils, topsoil, rock fragments, litter, and cacao leaf Cd concentrations from 30 farms. Results reveal generally low mean total soil Cd concentrations for topsoil and subsurface soils at 0.12 mg kg−1 and 0.05 mg kg−1, respectively. Leaf and litter Cd concentrations are significantly higher (p < 0.05) than soil Cd, with a mean of 0.42 and 0.4 mg kg−1, respectively. Our results suggest that age dependent surface-level processes such as the bioaccumulation and biocycling of Cd over time through the leaves, litter, and topsoil, govern Cd in the topsoil, leading to older cultivars and trees exhibiting higher Cd concentrations in leaves, litter, and soils. Subsurface soil Cd is primarily driven by geogenic Cd coming from the weathering of the underlying bedrock with a hypothesized contribution from pedogenic Cd being translocated to deeper soil horizons from the topsoil via clay and oxide illuviation. Our research provides insights into the accumulation of Cd in cacao plants and soils, which can lead to long-term preferential accumulation of cadmium on soil layers and thus increase plant uptake through roots.